Bullying versus creativity: Mutually exclusive workplace behaviors - Smith, George (Advances in Social Sciences Research Journal, 2017)
Applied creativity relies on workers who trust the environment and feel confident in making uncustomary strides to solve everyday problems. However, when employees face workplace bullying, the opportunity for true creativity is compromised as the brain is thrown into a flight or fight response, instead of a state that allows for creativity. Hence, this essay will discuss the behavioral response and brain damage experienced by the targets of workplace bullying. Recent studies show that true damage to the brain occurs for those dealing with intense stress on the job; in addition, damage to the organization occurs as well. Therefore, this essay reflects on how the creative process, which is needed in tough economic times, is truly compromised by workplace bullying.